KERJASAMA NEGARA-NEGARA ASEAN DALAM PENGENDALIAN PENCEMARAN UDARA LINTAS BATAS NEGARA DI LIHAT DARI HUKUM INTERNASIONAL - Raisa Rafina; Arif Arif; Jelly Leviza (Journal of USU International Law, 2013)
ABSTRACT At first, the environmental degradation/damage was only limited to the domestic level. But in a very short period of time, environmental damage began to explore the region and manage to affect international relations within ASEAN. Currently, most people are no longer in doubt that the environment is a major problem which makes it as an international issue. With the onset of the problem, causing a conflict between the ASEAN region. There are some cases that have an impact on international relations in the ASEAN region, one of which is the smoke pollution. Among some issues being raised were how the legal basis for cooperation among the ASEAN countries in controlling air pollution, how ASEAN cooperation in the control of environmental pollution in ASEAN and how the implications towards Indonesia due to agreement /cooperation in air pollution control. Results and discussion explaining  environmental pollution issues in ASEAN countries are basically generated from forest management activities result from excessive economic measures, especially among ASEAN countries in terms of the management and utilization of forests as an economic resource. Regulation of fog and smoke pollution in the international sphere can be seen from several declarations or conventions that exist. As in the 1972 Stockholm Declaration which recognizes the fundamental human right to be able to live in a good environment and healthy and as well as the obligation to maintain and be responsible in all actions to prevent pollution especially when it is very harmful to other countries, such as the prevention of burning forests that followed by the 1992 Rio Declaration and the 2002 World Summit in Johanesburg. And applied in the context of an international convention of The Geneva Convention The Convention on Long-Range Transboundary Air pollutants, 1979 (Geneva Convention, 1979), which in Article 2 obligates that States Parties to try to push as low as possible, gradually reduce and prevent air pollution including transboundary air pollution. Cooperation within ASEAN countries in controlling air pollution caused by forest fires can refer to the implementation of cooperation among ASEAN members. The cooperation ranging from the establishment of the ASEAN Agreement on the Conservation of Nature pollutan 1995, the Regional Haze Action Plan 1997, the ASEAN Agreement on Transboundary Haze Pollution in 2002 which is the world's first treaty that specifically addresses the cross-border pollution.   Keywords: Cooperation, ASEAN, air pollution, International Law